2019
DOI: 10.1371/journal.pone.0207472
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the severity of hypertension among Malaysian adults

Abstract: High blood pressure is a worldwide problem and major global health burden. Whether alone or combined with other metabolic diseases, high blood pressure increases the risk of cardiovascular disease. This study is a secondary data analysis from the National Health and Morbidity Survey 2015, a population-based study that was conducted nationwide in Malaysia using a multi-stage stratified cluster sampling design. A total of 15,738 adults ≥18-years-old were recruited into the study, which reports the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
1
21
0
3
Order By: Relevance
“…Similar to previous studies [ 20 ], we found that in the general population, a secondary/higher education was associated with a lower prevalence of hypertension and prehypertension. However, studies carried out in Bangladesh disagreed with our results [ 24 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies [ 20 ], we found that in the general population, a secondary/higher education was associated with a lower prevalence of hypertension and prehypertension. However, studies carried out in Bangladesh disagreed with our results [ 24 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous representative studies from Bangladesh [ 24 ] and India [ 25 ] have found an association between living in urban areas and hypertension, which was consistent with our results. In contrast, in Malaysia [ 20 ], rural areas were associated with a higher prevalence of hypertension. This association mainly depends on the social setting and definition of urbanization.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, about 1 billion people are living with hypertension as of today and according to the World Health Organization (WHO), this number expected to reach 1.56 billion people by 2025, covering 29.2% of the world’s population [ 6 ]. The worldwide occurrence of hypertension among adults rose sharply from 594 million in 1975 to 1.13 billion in 2015 [ 7 ]. In developed countries, 30% of the adult population is hypertensive, and this number is expected to increase to 60% in the coming decades [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, a chronic increase in blood pressure above 140/90 mmHg, remains a major health challenge and burden worldwide (Whelton et al 2017;Mahadir Naidu et al 2019). This disease is one of the major public health problems with global prevalence which increased from 594 million to 1.13 billion people in 1975 and 2015 respectively (NCD Risk Factor Collaboration 2017).…”
Section: Introductionmentioning
confidence: 99%